(untitled) (Eurasian Journal of Ecology, 2016)
The article gives the results of the growth rate of larvae Russian and Siberian sturgeon farmed in RAS Almatiskoy area. The results showed increased growth rate of Siberian sturgeon compared to Russian sturgeon.